고지방식이와 STZ 유도 제2형 당뇨 마우스에서 새싹의 항당뇨 효과 - 이현서(Hyun-Seo Lee); 강현주(Hyun Ju Kang); 전인화(In Hwa Jeon); 염정호(Jung Ho Youm); 장선일(Seon Il Jang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2014)
Sprout vegetables containing various types of polyphenols and flavonoids, are known to have anti-inflammatory, antioxidant, cholesterol-lowering, and anti-obesity activities. However, there have been few reports on the anti-diabetic efficacy of sprout vegetables. Here, we investigated the anti-diabetic effects of sprout extract obtained from buckwheat, beet, rape, broccoli, kohlrabi, red young radish, and dachai, in high fat diet (HFD) and streptozotocin (STZ)-induced type II diabetes mellitus mice. The mice were fed a HFD (60% calories as fat) for 8 weeks prior to intraperitoneal injection with STZ (75 mg/kg). The diabetic mice were divided into four groups: standard diet (STD, 10% calories fat), HFD, HFD with sprout extract (SPE) and HFD with metformin (MET). After 4 weeks, body weight gain was much lower in both SPE and MET groups than in HFD group. In contrast, there was no difference experiment groups regarding food intake ratio. The level of fasting blood glucose was significantly lower in the SPE and MET groups compared to the HFD group. Oral glucose tolerance and insulin tolerance in the SPE and MET groups were significantly ameliorated in comparison to the HFD group. The concentrations of serum total cholesterol, triglycerides, and LDL cholesterol in the SPE and MET groups were remarkably reduced in comparison to the HFD group, and HDL cholesterol concentration was higher in the SPE and MET groups than in the HFD group. Glutamate oxaloacetate transaminase and glutamate pyruvate transaminase levels were between SPE and HFD groups. The serum insulin and leptin concentrations were significantly reduced in both the SPE and MET groups compared to the HFD group. Therefore, these results indicate that sprout extract could improve insulin resistance and attenuate blood glucose level in HFD/STZ-induced type II diabetes mellitus mice. We conclude that this study may provide positive insights into sprout extract as a functional food ingredient for treatment of type II diabetes mellitus. 본 연구에서는 고지방식이와 streptozotocin으로 유도된 제2형 당뇨 마우스에서 새싹추출물의 항당뇨 효과를 살펴보았다. 제2형 당뇨 유도 후 4주 동안의 체중 변화를 관찰한 결과 새싹추출물군과 메트포민군에서 유의한 체중 감소 변화가 나타났으며, 식이섭취량에 따른 변화는 모든 실험군 간의 차이가 없었다. 공복혈당은 고지방식이군의 경우 실험종료일까지 지속적으로 상승하였고, 이와 대조적으로 새싹추출물과 메트포민군의 경우 실험 2주째부터 감소하여 실험 종료 4주째에서는 고지방식이군보다 유의적으로 감소하였다. 경구 내당능 검사는 포도당 섭취 후 60분, 90분, 120분에서 새싹추출물과 메트포민군이 고지방식이군보다 유의적으로 감소하였으며, 인슐린 내성 검사는 120분에서 새싹추출물과 메트포민군이 고지방식이군보다 유의성 있게 감소하였다. 혈중 지질 농도 변화에서 총콜레스테롤, 중성지방 그리고 LDL 콜레스테롤 농도는 고지방식이군에 비해 새싹추출물과 메트포민군에서 유의적으로 감소하였고, HDL 콜레스테롤 농도는 고지방식이군에 비해 새싹추출물과 메트포민군에서 증가하였다. 간독성의 지표인 glutamate oxaloacetate transaminase와 glutamate pyruvate transaminase 효소 활성도는 메트포민투여군과 고지방식이군을 제외한 실험군들 간에 유의성이 나타나지 않았다. 혈중 인슐린과 렙틴 농도는 고지방식이군에 비해 새싹추출물과 메트포민군에서 유의적으로 감소하였다. 이상의 결과를 바탕으로 새싹추출물은 제2형 당뇨 마우스에서 체중을 감소시키고 혈중지질 대사 이상을 조절하면서 인슐린 저항성을 감소시켜 혈당을 개선하므로 항당뇨 효과가 있는 우수한 식품 소재로서의 개발 가능성을 시사하고 있다.